The queer potential of the abject : The agency of matter and radical negativity in Mona Hatoum's Corps étranger - Martínez, Ariel; Arévalo, Luciano Nicolás; Gomariz, Tomás; Suzzi, Guillermo Sebastián (2021)
We present our thoughts here on British-Palestinian artist Mona Hatoum's Corps étranger (1994), a video-installation consisting of endoscopic images of the inside of the artist's own body projected from beneath the glass floor of a cylindrical booth. In a departure from the social constructionist proposal of Judith Butler, who emphasizes the role normative ideals play in the construction of the body by imposing an imaginary morphological ideal (assigning some parts of the body to a position in a hierarchy while dismissing others), this performative work of art is analyzed in the light of an emerging theoretical field known as New Materialism. Using this perspective, a return to materiality is proposed as a counterpoint to hyper-constructionist queer thought, presented here as inadequate for addressing the complexity of the agency of matter and its relation with meaning. Similarly, and in agreement with criticism of that sector of queer theory which revolves around representation and silences or demonizes materiality and its processes, we suggest connections between material agency and antisocial queer negativity, which some theorists link to the death drive. On the basis of these theoretical connections, we utilize some non-essentialist viewpoints of the body that enable us to see that Hatoum's video-installation confronts us with a corporal dimension which manifests itself as an eruption of matter outside the limits of linguistic mediation. Corps étranger constitutes a potent onto-epistemological resource that brings us closer on the one hand to integrating the agency of matter into the definition of what it is to be human, and on the other, to the recovery of queer theory's potential to make peace with dimensions that cannot be confined to the limits of language.
Keywords: Body; Abject; Matter; Presentation; Psychoanalysis